Story of blind baba abdalla - Kumar Anu (Mumbai Macaw Books, 2010)
"Blind Baba Abdalla" by Macaw Books is an inspiring children's story about a wise and compassionate blind man named Baba Abdalla. Despite his blindness, Baba Abdalla is known for his wisdom and ability to help others in his community. The story follows his interactions with various people who seek his guidance and highlights his profound understanding and problem-solving abilities. Through his kindness and insight, Baba Abdalla demonstrates that true vision comes from the heart and mind, not just the eyes. The book teaches valuable lessons about empathy, inner strength, and the importance of wisdom over physical sight.